Farming groups and empowerment of women smallholder farmers. Issue 5 (4th July 2021) - Othman, Mwanajuma S.; Garrod, Guy; Oughton, Elizabeth
ABSTRACT: Discrimination and subordination of women have contributed to lower economic and social development levels for women, especially in developing countries. Empowerment of women enables them to gain control of their lives by increasing their participation in the economy and all levels of decision making. This study used mixed method research to examine the social and economic empowerment of women experienced in farming groups. The groups have contributed to women's empowerment. However, the individual abilities of women are vital for empowerment to occur among members. Development support organisations should focus on improving women's capabilities alongside the mobilisation of group establishment.